LANGUAGE AND IDENTITY: A SOCIOLINGUISTIC APPROACH - Kalbayev Abdulaziz Shavkatovich; Abduramanova Diana Valerevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article explores the relationship between language and identity from a sociolinguistic perspective, highlighting how language functions as both a tool for expressing and negotiating individual and group identities. Language is not merely a medium of communication; it is deeply intertwined with social factors such as gender, ethnicity, class, and region, which shape how people define and represent themselves. The essay examines how language varieties, including dialects and accents, reflect social and cultural affiliations, and how practices like code-switching reveal the dynamic nature of identity. Furthermore, the paper investigates how gendered language use reinforces traditional roles and how ethnicity and social class impact linguistic identity and social mobility